2014
DOI: 10.1111/lnc3.12116
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Categories in Sociolinguistic Studies of US Latino Communities

Abstract: This article provides an overview of the diversity of Latino communities in the USA and examines how issues of ethnicity and identity have been treated in representative recent studies. The article offers suggestions for coding information about identity and ethnic orientation that will enable researchers to go beyond overly general and often contested superordinate terms. Finally, the article shows how newer methods of statistical analysis provide the means for a more fine‐grained coding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, one unfortunate weakness of the present collection is that this small set of papers underestimates the true complexity of 'ethnic identity'. For example, even limiting the definition of 'ethnicity' to racial or regional heritage, one of the glaring absences here is a discussion centered on Latino/Latina identities, which have been especially foundational to the body of research problematizing the ethnolect concept (Toribio 2000(Toribio , 2003Fought 2006;Eckert 2008a;Jaspers 2008;Mendoza-Denton 2008;Bayley forthcoming;Otheguy et al 2007). No Native American or First Nations groups are represented here (but see, e.g., Dannenberg and Wolfram 1998), nor is 'ethnicity' based on religious heritage (but see, e.g., Benor 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, one unfortunate weakness of the present collection is that this small set of papers underestimates the true complexity of 'ethnic identity'. For example, even limiting the definition of 'ethnicity' to racial or regional heritage, one of the glaring absences here is a discussion centered on Latino/Latina identities, which have been especially foundational to the body of research problematizing the ethnolect concept (Toribio 2000(Toribio , 2003Fought 2006;Eckert 2008a;Jaspers 2008;Mendoza-Denton 2008;Bayley forthcoming;Otheguy et al 2007). No Native American or First Nations groups are represented here (but see, e.g., Dannenberg and Wolfram 1998), nor is 'ethnicity' based on religious heritage (but see, e.g., Benor 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we should not conflate the following: Linguistic heritage – as in the papers by Wong & Hall‐Lew and Bayley in this issue. Regional heritage – as in the papers in this issue by Wong & Hall‐Lew, Bayley and Blake, where studies have considered religion and regional heritage separately they have shown that each is independently variable. Of course, it is a mistake for researchers to assume a strong interdependence between religion and linguistic or regional heritage (e.g., Pandharipande ; Hary and Wein : 87, Kulkarni‐Joshi , forthcoming). Religious heritage and present religious adherence.…”
Section: ‘Ethnicity’ and ‘Religion’ Are Not Synonymous And ‘Religionmentioning
confidence: 97%
“…Existing literature thus unanimously contends that ethnic identity influences the development of ethnolinguistic variables and the adoption of regional features by minority groups. However, much of the work investigating ethnolinguistic variation has focused on variation across , rather than within , broad demographic categories, which has led to the common use of labels, such as ‘Black’, ‘White’, ‘Latino’, and ‘Asian’, as covering a whole range of potentially disparate backgrounds (Bayley , Blake , Hall‐Lew and Wong ). These ethnoracial labels create an impression of homogeneity within minority groups, both in terms of speakers’ ethnic identity and its reflection in speech.…”
Section: Introductionmentioning
confidence: 99%